Development of an observational tool to assess health coaching fidelity. Issue 3 (March 2021) - Sohl, Stephanie J.; Lee, Deborah; Davidson, Heather; Morriss, Blaire; Weinand, Rebecca; Costa, Katherine; Ip, Edward H.; Lovato, James; Rothman, Russell L.; Wolever, Ruth Q.
Highlights: Developed the Health Coaching Index to assess fidelity to practical coaching skills. An interclass correlation among three coders of 0.81 showed excellent agreement. Correlations with Roter Interaction Analysis System variables demonstrated validity. The HCI may facilitate robust training of health coaches. Abstract: Objective: This study describes the development of the Health Coaching Index (HCI), an observational tool for assessing fidelity to implementing health coaching practical skills. Methods: Initial HCI items were developed, adapted following cognitive interviews, and refined during coding training. Participants (n = 42) were trainees who completed a National Board for Health and Wellness Coaching (NBHWC)-approved training program and coached a standardized patient. Interrater reliability for the HCI was determined by calculating interclass correlations from ten videos coded by three raters. Construct validity was evaluated from 42 recordings using Spearman's Rho between HCI and Roter Interaction Analysis System (RIAS) codes. Results: The interclass correlation (ICC) for HCI total score was 0.81, considered an excellent level of inter-rater agreement. Some significant correlations between HCI and RIAS codes supported construct validity (e.g., patient activation: Rho = 0.32; empathy: Rho = 0.36). Conclusion: The HCI total score can reliably be used to assess fidelity to health coaching skills, and the HCI has construct validity similar to the RIAS as a measure of patient activation. Practice Implications: Adoption and further study of the HCI tool will allow for a more consistent implementation of health coaching skills, and may facilitate more robust training of health coaches for clinical practice and research.